Agony in the pulpit : Jewish preaching in response to Nazi persecution and mass murder 1933-1945 - Saperstein, Marc, 1944- 1944- Herausgeber Verfasser einer Einleitung (Hebrew Union College Press, 2018)
"Selections, as well as complete sermons, preached in synagogues, at rallies, etc., both in the US and Europe, from 1933-1945, showing the increasing awareness of, and reactions to, Jewish persecution in the years before and during WWII"--